2009
DOI: 10.1007/s00264-009-0891-1
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous fixation of selected scaphoid fractures by dorsal approach

Abstract: The aim of our study was to evaluate clinical, radiological and functional outcomes of selected cases of percutaneous fixation of scaphoid fractures via a dorsal approach. Percutaneous fixation by dorsal approach was done in 32 patients (mean age 32.2 years) involving both fresh and late scaphoid fracture presentations (mean 17 days). Fourteen cases of B1 type, ten cases of B2 and eight cases of C type (Herbert's classification) were treated. The patients were prospectively followed up clinically and radiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 27 publications
3
22
0
3
Order By: Relevance
“…However, open approaches, either dorsal or palmar, have some certain problems including soft tissue stripping, damage to ligaments, especially radioscaphocapitate and radiolunate ligaments leading to instability, injury to the already damaged blood supply leading to AVN, infection, reflex sympathetic dystrophy, painful scar formation and stiffness [1-6, 8, 10-12]. For these reasons, there has been a trend towards percutaneous fixation of such fractures [2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, open approaches, either dorsal or palmar, have some certain problems including soft tissue stripping, damage to ligaments, especially radioscaphocapitate and radiolunate ligaments leading to instability, injury to the already damaged blood supply leading to AVN, infection, reflex sympathetic dystrophy, painful scar formation and stiffness [1-6, 8, 10-12]. For these reasons, there has been a trend towards percutaneous fixation of such fractures [2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature revealed a limited number of case series of dorsal percutaneous fixation of scaphoid delayed or nonunions [2][3][4][5] and none of them reported AVN. On the other hand, AVN is the most important complication of scaphoid fractures and occurs due to the disruption of precarious blood supply [1,8], and the risk for AVN increases if the fracture is left untreated [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown in biomechanical and clinical study that central placement of a scaphoid screw improves the healing rate and reduces the immobilisation period of a scaphoid fracture [10,13,18]. Trumble et al [18] reported that the scaphoid screw located in the central scaphoid was associated with shorter union time based on their clinical data of 34 patients.…”
Section: Discussionmentioning
confidence: 99%
“…presentations with dorsal approach. 20 Similarly Shin AY et al found that the fracture union occurred at an average of 7.1 week compared to 11.6 weeks with cast treatment using volar percutaneous fixation for stable scaphoid fracture. 23 Reported union rates and complication rates with the percutaneous technique ranged from 94% to 100% and 0% to 30%, respectively.…”
Section: Original Articlementioning
confidence: 96%